A study on ceiling jet characteristics in an inclined tunnel. (August 2015) - Huo, Y.; Gao, Y.; Chow, W.K.
Highlights: Characteristics of a ceiling jet of an inclined tunnel in a fire were studied. Scale modeling experiments on a ceiling jet in a model tunnel were carried out. Numerical studies by large eddy simulation were performed. Air temperature and flow velocity were studied along the tilted tunnel. Comparison made with the results by empirical equations reported in literature. Abstract: The characteristics of a ceiling jet of an inclined tunnel in a fire will be studied and reported in this paper. Scale modeling experiments on a ceiling jet in a model tunnel of length 3.0 m, width 0.8 m and height 1.0 m inclined at different angles of 0°, 10°, 20° and 30° were carried out. Numerical studies by large eddy simulation were then performed. Both experimental observation and numerical simulation indicated that the characteristics of the temperature and velocity fields near the upper tunnel are different from those obtained using the empirical equations reported in the literature. Another set of empirical equations for gas temperature and flow velocity along the tunnel were fitted by experimental data. These derived empirical equations are useful for estimating the temperature and flow velocity patterns for the ceiling jet in an inclined tunnel with an angle within the range 0–30°.